2016
DOI: 10.1186/s12891-016-1041-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between gastrointestinal events and osteoporosis treatment initiation in women diagnosed with osteoporosis in France: a retrospective analysis

Abstract: BackgroundA substantial portion of women diagnosed with osteoporosis (OP) do not initiate pharmacotherapy to reduce fracture risk. In clinical practice, gastrointestinal (GI) events have been linked with OP therapy discontinuation. However, there is limited research examining GI events as barrier to treatment initiation following an OP diagnosis. The objective of this study was to examine the association between gastrointestinal (GI) events and osteoporosis (OP) treatment initiation among post-menopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…There was no significant difference of BMD between peer group of the same ethnic and geographical environment [8,9], while the BMD datas from different races cannot be shared. Recently almost all the laboratory used "Oriental" reference databases which were configured by imported instrument factory to diagnose OP, and the results of the accuracy and reliability were affected by them [10]. This research report provided BMD reference range in the shandong's coastal areas.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference of BMD between peer group of the same ethnic and geographical environment [8,9], while the BMD datas from different races cannot be shared. Recently almost all the laboratory used "Oriental" reference databases which were configured by imported instrument factory to diagnose OP, and the results of the accuracy and reliability were affected by them [10]. This research report provided BMD reference range in the shandong's coastal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Their efficacy in increasing bone mineral density (BMD) and normalizing bone turnover is well established in postmenopausal osteoporosis (PMO) and glucocorticoid-induced osteoporosis (GIOP) [ 7 ] and approximately 50% of osteoporotic fractures can be prevented through the use of BPs [ 8 ]. A recent meta-analysis also demonstrated that BPs can preserve BMD and prevent vertebral fractures in patients with rheumatic diseases including RA [ 9 ], however, due to lack of patient education regarding the risks related to osteoporosis, gastrointestinal adverse effects and the complexity of the recommended regimen, adherence with oral BPs has been reported to be suboptimal in clinical practice [ 10 12 ], which consequently increases the risk of osteoporotic fractures by 30–40% [ 13 ]. Thus, poor adherence with oral BPs can mitigate their therapeutic benefit and is a significant clinical burden [ 14 ].…”
Section: Introductionmentioning
confidence: 99%